Intrinsic concentration dependences in the HgCdTe quantum well in the range of the insulator-semimetal topological transition - Melezhik, E.O.; Gumenjuk-Sichevska, J.V.; Dvoretskii, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The band structure and dependences of the intrinsic concentration in the
mercury-cadmium-telluride (MCT) Hg₀.₃₂Cd₀.₆₈Te/Hg₀ Cd₀ Te/Hg₀.₃₂Cd₀.₆₈Te quantum
wells in the framework of the 8x8 k.p envelope function method on the well width L and
composition x were calculated. Modeling of the energy spectra showed that the intrinsic
concentration can vary about an order of magnitude with variation of the well width and
chemical composition in the range of x < 0.16 and well width L < 20 nm at the liquid
nitrogen temperature. These strong variations of the carrier concentration are caused by
the insulator-semimetal topological transition.